The Effect of Eight Weeks of Training and Two Weeks of Detraining in Office on Vaspin and Glycemic Indices of Male Staff - Seyed Ali Hosseini; Ammar Bagheri; Maliheh Izadi; Omidreza Salehi; Fatemeh Farkhaie (Salāmat-i kār-i Īrān, 2019)
Background and Aim: Adipose tissue is biologically superior to energy storage and an active tissue and secretes proteins such as vaspin, called adipokine. The relationship between fatty tissue and other biological systems of the body is through the expression of some bioactive molecules called adipocytokines. Adipokines are involved in various metabolic processes, including appetite regulation, insulin sensitivity and insulin secretion, energy expenditure, cardiovascular function, and inflammation. Vaspin can be considered as an adipokine derived from internal adipose with insulin sensitivities. In humans, vaspin serum concentrations are associated positively with age, body mass index, and insulin sensitivity disorder. Vaspin is a serine protease inhibitor family discovered in 2005 and has a composition of 392 to 395 amino acids. This adipokine was found in the visceral fat tissue of rat, a model of obese animals with type 2 diabetes. Vaspin plays a very important role in the pathogenesis of nonalcoholic fatty liver disease. This substance not only regulates the amount of insulin sensitivity, but also acts as a mediator of inflammatory processes. It has also been reported that vaspin circulation is associated with gender, body fat percentage, glucose, insulin, and insulin resistance. It has been reported that vaspin by reacting oxygen inhibitors can inhibit the inflammatory state of smooth muscle cells. Increasing blood glucose results in oxidative stress, which in turn results in the activation of the nuclear factor and thus an increase in the level of pre-inflammatory cytokines in the bloodstream. Consumption of vaspin in obese rats with high fat diet resulted in improved glucose tolerance and insulin sensitivity and inversely altered expression of genes that are dependent on insulin resistance. Animal studies suggest that effecting vaspin on insulin sensitivity increases its effect on adipose tissue. Therefore, it is suggested that the incremental regulation of vaspin suggests a compensatory mechanism against insulin resistance. Sports activities and healthy living today are topics that we have heard or read much more in a variety of ways about their importance. In fact, most people in the world do sports and physical activity in different ways; however, with the mechanization of lifestyle communities, more people go to inertial and sedentary environments. The results of the researches confirm the theory that all people are convinced that exercise is essential for health and well-being and also regular physical activity is essential for themselves and their children. Few studies have been conducted on the effect of sports activity on vaspin and glycemic indices, which have contradictory results, some suggesting that sports activities increase, decrease or without changes in the levels of vaspin. Therefore, due to the limited and controversial studies and the importance of not engaging in sports activities, this study aimed to investigate the effect of eight weeks of aerobic training and two weeks of detraining on levels of vaspin, glucose, insulin and insulin resistance in inactive men.